Desarrollo de una aplicación web progresiva para incentivar el turismo en las parroquias rurales del cantón Latacunga - Sánchez Jaque, Johana Maribel (2022)
The current technological proposal was made with the aim to develop a Progressive Web Application (PWA) to encourage tourism in the Latacunga Canton rural parishes. Research methodologies different types were used, such as bibliographic research, what allowed exploring related concepts with the topic for building the theoretical framework and helped to acquire the necessary knowledge for PWA development; the field investigation helped to keep direct communication with the interested parties, furthermore, it was applied interviews as a technique to identify the problem and define the system functionalities. For application construction was used agile practices, such as the Product Backlog, User Stories, Sprint, Release Plan and Business Process Modeling (BPMN) diagrams, in order to reduce documentation and generate value deliveries, continuously; the application architecture consists of the developed Frontend with HTML, CSS and Angular; the Backend, where were used the Python language, through the Django and Django Rest Frameworks, the database manager is PostgreSQL. This way, it was got a Progressive Web Application, that is currently, is found production and accessible, since the link https://turismo-rural-latacunga.web.app; actually, the project has the implementation letter, whose verifies compliance with the requested application functionalities by interested parties.